2022
DOI: 10.1155/2022/3098726
|View full text |Cite|
|
Sign up to set email alerts
|

The Efficacy and Safety of Bisoprolol in the Treatment of Myocardial Infarction with Cardiac Insufficiency

Abstract: Background. Bisoprolol is commonly used to treat moderate or severe chronic stable heart failure, coronary heart disease, and hypertension. This study is aimed at analyzing the efficacy of bisoprolol in the treatment of myocardial infarction with cardiac insufficiency and its effect on cardiac function, Hcy, and CRP through meta-analysis. Methods. A total of 120 patients with myocardial infarction and cardiac insufficiency from February 2020 to February 2021 were selected and randomly divided into two groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…and promoting the production of human insulin, thus resisting human inflammation, improving vascular sclerosis, increasing the blood supply function of the heart, avoiding myocardial hypoxia and regulating the state of smooth muscle, making the heart gangrene partially regenerate, expanding the coronary vessels of the heart, and dredging the blood accumulated in the pulmonary circulation, make blood circulation more smooth, so as to improve left heart function. Sacubitril-valsartan is a new type of angiotensin-enkephalin inhibitor [24,25] . Patients can degrade the natriuretic peptide after taking it orally, so as to improve the level of natriuretic peptide in the body, and then play the role of water excretion, vasodilation and inhibition of sympathetic system [26] .…”
Section: Table 3: Analysis Of Treatment Effectiveness Of Patients In ...mentioning
confidence: 99%
“…and promoting the production of human insulin, thus resisting human inflammation, improving vascular sclerosis, increasing the blood supply function of the heart, avoiding myocardial hypoxia and regulating the state of smooth muscle, making the heart gangrene partially regenerate, expanding the coronary vessels of the heart, and dredging the blood accumulated in the pulmonary circulation, make blood circulation more smooth, so as to improve left heart function. Sacubitril-valsartan is a new type of angiotensin-enkephalin inhibitor [24,25] . Patients can degrade the natriuretic peptide after taking it orally, so as to improve the level of natriuretic peptide in the body, and then play the role of water excretion, vasodilation and inhibition of sympathetic system [26] .…”
Section: Table 3: Analysis Of Treatment Effectiveness Of Patients In ...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%